On interim performance evaluations and interdependent period outcomes - Christian Lukas (Journal of Management Control, 2023)
Performance feedback is an integral element of an accounting system, and firms provide this feedback at varying frequencies to their employees. This paper explicates the impact of an interim performance evaluation on the principal's surplus using a dynamic two-period agency model. Two settings are discussed: single-purpose use, wherein accounting information is used solely for control purposes, and dual-purpose use, in which accounting information is used for production and control. Results demonstrate that the optimality of interim performance evaluations depends on the use of information and the interdependence of period outcomes. Furthermore, neither setting entails strict dominance with regard to carrying out interim evaluations or not. It implies that an interim evaluation can be optimal even if the optimal course of action does not depend on it. It further suggests that refraining from the interim review can be optimal even if that information is required to determine the optimal effort level.
Keywords: D86; M12; M41; M52; 330; Agency; Aggregation; Frequency; Dual-purpose; Single-purpose; Interim evaluation; Accounting information